UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SDN 12 SUNGAI LIMAU - Suryenti, Suryenti (Jurnal Manajemen Pendidikan, 2017)
Based on observations that researchers have done in SDN SDN 12 Sungai Limau, it was found that teachers' ability in improving teacher pedagogic competence is still low. The purpose of this study is to describe and obtain information about reminding teacher pedagogic competence. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 8 teachers of SDN SDN 12 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results showed that with Academic Supervision can Pedagogikguru Competence In SDN SDN 12 Sungai Limau.Hal this is proved by the Academic supervision can Increase pedagogic competence of teachers In SDN SDN 12 Sungai Limau from cycle I to cycle II. The average ability of teachers in improving the making of RPP in cycle I is 51.30 with less category, In cycle II is 84.47 Good.